Analysis Of Predisposing, Enabling And Reinforcing Factors With The Implementation Of The Role Of Cadad In Prevention Stunting In The Lombok Central Region Region West Nusa Tenggara - Asmawati Asmawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The occurrence of anemia in adolescents due to lack of nutrients transport and oxygen throughout body to be inhibited, in the brain this causes a decrease in the level of concentration. This decrease in concentration level is more severe if anemic sufferers have low emotional intelligence because it is increasingly difficult for adolescents to carry out a concentration of mind. The purpose of this study is to influence the incidence of anemia and emotional quotient on the level of student learning concentration of Pule 1 Senior High School Trenggalek Regency. The design of this research is correlational analytic with cross sectional approach. Data collected by questionnaire an dobservastion sheet, data analysis by ordinal regression test at α = 0.05. The results showed that there was an influence of anemia against concentration level in SMAN 1 Pule in Trenggalek Regency (p-value = 0,000), there was an emotional quotient effect against concentration level in SMAN 1 Pule in Trenggalek Regency (p-value = 0.011) and together there is an influence of the incidence of anemia and emotional quotient against concentration level in Pule 1 Senior High School, Trenggalek Regency (p-value = 0,000). Adolescents who experienced anemia will experience a decrease in the body's metabolism because one component of metabolism that is oxygen cannot be supplied smoothly so that the body's energy decreases, especially in the brain will have an impact on decreased concentration in the learning process. Relation to emotional intelligence, through good emotional intelligence, a student can manage his time well so that he is able to place the utilization of the time he has for his main task of learning. Through emotion management, EQ plays a role in supporting self-control and time management so that students who have high EQ will not be easily affected by environmental disturbances so that they can carry out the learning process with good concentration